1995
DOI: 10.1007/bf01271531
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neuronal acetylcholine nicotinic receptor ?4 and ?2 subunits during postnatal development of the rat brain

Abstract: The expression of the alpha 4 and beta 2 subunits of neuronal nicotinic acetylcholine receptors (nAChRs) was studied in developing rat brain using in situ hybridization. The levels of both transcripts were already high at birth in cerebral cortex, medial habenula, CA1/CA3 regions of the hippocampus and several thalamic nuclei. In general, the beta 2 subunit showed a higher density of hybrids than the alpha 4. Beta 2 expression did not change with age in the medial habenula, medial geniculate nucleus or in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Extensive work using immunohistochemistry and in situ hybridization in chick, mouse, rat, and rabbit have identified several subunits of nAChRs in the retina. There is expression of several subunits that comprise heteromeric nAChRs in the IPL, including the ␣3-6 (and ␣8 in chick) and ␤2-4 subunits (Swanson et al, 1987;Hoover and Goldman, 1992;Keyser et al, 1993;Hamassaki-Britto et al, 1994;Cimino et al, 1995;Zoli et al, 1995;Vailati et al, 1999;Champtiaux et al, 2002). Both mRNA and protein have been localized to several cell types in the inner retina, including RGCs, amacrine cells, displaced amacrine cells, and bipolar cells.…”
Section: Cholinergic Network In the Developing Vertebrate Retinamentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive work using immunohistochemistry and in situ hybridization in chick, mouse, rat, and rabbit have identified several subunits of nAChRs in the retina. There is expression of several subunits that comprise heteromeric nAChRs in the IPL, including the ␣3-6 (and ␣8 in chick) and ␤2-4 subunits (Swanson et al, 1987;Hoover and Goldman, 1992;Keyser et al, 1993;Hamassaki-Britto et al, 1994;Cimino et al, 1995;Zoli et al, 1995;Vailati et al, 1999;Champtiaux et al, 2002). Both mRNA and protein have been localized to several cell types in the inner retina, including RGCs, amacrine cells, displaced amacrine cells, and bipolar cells.…”
Section: Cholinergic Network In the Developing Vertebrate Retinamentioning
confidence: 99%
“…A possible explanation for the absence of layers in ␤2Ϫ/Ϫ mice is that, independent of retinal activity, nAChR signaling in the LGN itself (Cimino et al, 1995;Zhu and Uhlrich, 1997;Lena and Changeux, 1999) may be required. However, this is unlikely, because injection of nAChR antagonists into the ventricles in ferret do not prevent layer formation (Penn et al, 1998).…”
Section: Role Of Nachr-mediated Waves In Retinogeniculate Developmentmentioning
confidence: 99%
“…Moreover, the inactivation of the gene coding for the nAChR p2 subunit provides mutant mice with several characteristic alterations at the molecular, cellular and behavioural levels (Picciotto et uZ., 1995). Numerous in ,~i t u hybridization studies have been performed in order to detect the neuronal nAChR subunits present in the nervous system of the adult (Goldman et al, 1986;Wada et al, 1989Wada et al, , 1990Dineley-Miller and Patrick, 1992;SCguila et al, 1993;Rust et al, 1994;Cimino et al, 1995) and embryonic (Zoli eb al., 1995) rat. Yet, the distribution of a6 mRNA has not been described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotinic binding affinity in cortical areas including the V1 also rapidly increase starting the first postnatal week, but then peak after the second week before moderately declining to reach adulthood levels by the end of the third week(Kumar and Schliebs, 1992; Zhang et al, 1998; Tribollet et al, 2004; Doura et al, 2008). Cortical expression of nicotinic acetylcholine receptors (nAChR), including the most common heteromeric α4β2 and the homomeric α7 nAChRs, are also known to undergo rapid increases during early postnatal development (Fuchs, 1989; Kumar and Schliebs, 1992; Bina et al, 1995; Broide et al, 1995, 1996; Cimino et al, 1995). Previous work in the V1 of P12 mice have found that transiently enhanced nicotinic transmission through β2 and α7 nAChRs of the layer VI are necessary for deep layer spine formation and glutamatergic synapse maturation respectively and independently of one another.…”
Section: Postnatal Development Of Visual Cortex Cholinergic Neurommentioning
confidence: 99%